Kajian Normatif Perencanaan Penataan Ruang dan Penatagunaan Tanah - Arba -; L. Syapruddin; Diangsa Wagian (Jatiswara, 2015)
This research aims to normatively study and analyze the government’s obligation to make spatial planning and land use management; and also to review and analyze the legal conception of spatial planning and land use management in accordance with the legislations existing in Indonesia. This study is normative, i.e. a research which examines the fundamentals/principles of law, review the norms and legal concepts regulating spatial planning and land use management. This research applies normative approach; there are statute approach, conceptual approach, and comparative approach. It uses library resources which consist of primary, secondary, and tertiary legal materials. The research discovers that government is required to establish spatial planning and land use management on the basis of philosophical, juridical, and empirical foundations. Furthermore, spatial planning is a process to determine the spatial structure and pattern which covers the arrangement and establishment of the spatial plan. While the land use management is a pattern of the land use management which covers possession, use and utilization of land which constitute land use consolidation through institutional arrangements associated with the use of land as an integrated system for the benefit of a fair society. Spatial planning and land use management is an integral and inseparable, as land use management is part of the spatial plan, so that they are actually under the same legal basis. This research recommends that spatial planning and land use management should fully be committed to create the spatial and land utilization and also natural resources effectively and efficiently.